Effect of the nanometric LiFePO4 on the hydrogen storage properties of MgH2 - Cheng, Y.; Zhang, W.; Liu, Jian; Cheng, K.; Zhao, Z. (Elsevier Ltd, 2017)
A nanometric phosphoric complex salt additive was synthesized by hydrothermal method. Its catalytic effect on the hydrogen storage properties of MgH2 was investigated. MgH2+20 wt.% LiFePO4 obtained by ball-milling process had an ability of absorbing 2.03 wt.% hydrogen at 423 K in 21 min, and only 0.98 wt.% could be absorbed by MgH2 for the identical condition. 3.61 wt.% hydrogen could be released by the composite at 623 K in 21 min, whereas only 2.23 wt.% was desorbed by as-received MgH2. Doping by nanometric LiFePO4 expressively enhanced the hydrogenation/dehydrogenation properties of MgH2, and changed the rate-controlling steps from three-dimensional interfacial reaction to one-dimensional diffusion process. Meanwhile, the onset dehydrogenation temperature for MgH2+20 wt.% LiFePO4 was 653 K, which was found to be 60 K lower than the as-received MgH2. In addition, the addition of LiFePO4 also lowered the activation energy (Ea) 31 kJ mol-1. Based on XRD and XPS analysis, the in situ formed phases LiMgPO4 and Fe, which are produced by the reaction between MgH2 and LiFePO4, may be responsible for the remarkable improvement in hydrogen storage properties of MgH2.